Pengaruh Kepadatan Bagan Dan Kedalaman Perairan Terhadap Produktivitas Hasil Tangkap Bagan Tancap Di Teluk Pang Pang, Banyuwangi, Jawa Timur - Rani Ekawaty (Journal of Marine and Aquatic Sciences, 2015)
During 1998-2003 fisheries production tends to decrease for Muncar, Banyuwangi, East Java. Growing number of fishing gears (especially the set fishing gear like the bambbo platform lift net) in the Pang Pang bay even though its presence is not allowed, this is might be the caused of the decreased fisheries production. As for the bamboo platform lift net itself has many factors that affect the catch effort productivity. Some of them were examined in this study which are the density (unit/ha), water depth (m) and time of hauling (min). From this study, we expected to know how far the influence of each factors as well as the mathematical models of it. This study results shows that the density of the bamboo platform lift net greatly affect the fishing gear productivity, that the higher the density number will lead to further decline in the fishing gear productivity. The water depth also has an effect, in which the deeper the waters of the fishing gear, the more catch result get. The other factors such as the time dummy and hauling time influence less on the catch. The optimum density number is < 5unit/ha, as the optimum water depth is ? 26,2 m.